Mites Trichouropoda and Uroobovella spp. (Uropodoidea) phoretic on bark beetles (Scolytinae): a comparison from a declining mountain spruce forest in Central Europe. Issue 4 (18th May 2016) - Zach, Peter; Kršiak, Branislav; Kulfan, Ján; Parák, Michal; Kontschán, Jenő
ABSTRACT: Mites of the genera Trichouropoda and Uroobovella are characteristic associates of bark beetles which act as agents of their dispersal in many types of forest ecosystems worldwide. We compared the phoretic assemblages of Trichouropoda and Uroobovella mites on six species of bark beetle associated with Norway spruce ( Picea abies (L.) Karsten), namely: Dryocoetes autographus Ratzeburg, Hylastes cunicularius Erichson, Hylurgops palliatus (Gyllenhal), Ips typographus (Linnaeus), Pityogenes chalcographus (Linnaeus) and Polygraphus poligraphus (Linnaeus). Bark beetles were caught at random in non-baited flight-interception traps set in the shrub layer of a declining mountain spruce forest in the Tatra Mountains, West Carpathians, Central Europe. Over four years of a bark beetle outbreak, a total of six species of mites and 12 phoretic associations between mites and beetles were recorded. A newly documented host association includes that of Trichouropoda pecinai Hirschmann & Wiśniewski with H. palliatus . The most frequently recorded mite-beetle associations were: T. pecinai with H. cunicularius, Trichouropoda obscura (Koch) with H. palliatus, Trichouropoda polytricha (Vitzthum) with P. chalcographus and I. typographus and Uroobovella vinicolora (Vitzthum) with D. autographus . The results suggest that most of the recorded mite species have distinct bark beetle dispersants and that niche partitioning in these dispersants may be reflected by the observed mite–host associations.